Supporting marine spatial planning with an ecosystem model of Algoa Bay, South Africa. Issue 2 (3rd April 2022) - Ortega-Cisneros, K; Weigum, E; Chalmers, R; Grusd, S; Lombard, AT; Shannon, L
Abstract : The Ecopath with Ecosim (EwE) modelling framework was used to develop a model of Algoa Bay and test the ecosystem impacts of the implementation of the Addo Elephant National Park Marine Protected Area (MPA). The Ecopath model included 37 functional groups ranging from phytoplankton to top predators and was fitted to 12 and 14 time-series of biomass and landings, respectively, from 2010 to 2019 (calibration period), using Ecosim. Two scenarios representing different degrees of fisheries closures in the MPA were explored through a 30% and a 100% reduction in fishing effort. Temporal simulations were run until 2059. The fitting procedure identified the best-fit model as the one including the effects of fishing, the six most-sensitive predator–prey interactions, and environmental forcing (primary production anomaly on small phytoplankton). Overall, the predicted biomass and catch time-series reasonably reproduced the observed time-series for 2010–2019, with the biomass of sardine Sardinops sagax, round herring Etrumeus whiteheadi, and African penguins Spheniscus demersus showing the best fits to data. Both MPA scenarios resulted in higher total biomass compared with the baseline by the end of the simulation and decreased catches due to less fishing effort. The most profound biomass increases under the MPA scenarios were observed in apex and pelagic elasmobranchs, yellowtail Seriola lalandi and African penguins. Future research is needed to improve the more-uncertain model parameters and include other key sectors in Algoa Bay, such as shipping. However, this model provides a good foundation for future work including the application of spatially explicit modelling of the bay using Ecospace.